National Innovation System and the Development of Scientific and Innovation Policy in the Republic of Armenia - Khnkoyan, A. (Наука та інновації, 2012)
The paper deals with an overview of developments in S&T and innovation sectors in Armenia during the last decade. Adopted policy documents directed to promote innovation processes and development of national innovation system, and analysis of the government actions towards addressing the pressing challenge of reformation of S&T and innovation system in accordance with the requirements of the needs of economic development of the country are presented.